Oriented Strontium Carbonate Nanocrystals within Collagen Films for Flexible Piezoelectric Sensors. (8th August 2021) - Fang, Weijian; Ping, Hang; Li, Xinhui; Liu, Xiaofei; Wan, Fuqiang; Tu, Bingtian; Xie, Hao; O'Reilly, Patraic; Wang, Hao; Wang, Weimin; Fu, Zhengyi
Abstract: Bone, assembled by mineralized collagen fibrils, displays piezoelectric properties under external stimulation to affect tissue growth. The mineralized collagen fibrils consist of collagen and oriented inorganic nanocrystals. Inspired from the unique structures and piezoelectric effect of mineralized collagen fibrils, the intrafibrillar mineralization of oriented strontium carbonate nanocrystals is achieved in vitro, which also exhibits good piezoelectric properties. The amorphous strontium carbonate precursors penetrate from the gap zones and fill gradually into the whole space within the collagen fibrils, and transform into a co‐oriented crystalline phase. Isolated mineralized collagen fibrils with organized SrCO3 nanocrystals acquire good flexible properties and inverse piezoelectric responses with an effective piezoelectric coefficient of 3.45 pm V −1, much higher than individual collagen (1.12 pm V −1 ) and SrCO3 crystals (0.092 pm V −1 ). These results may indicate that the organic and inorganic components synergistically contribute to the piezoelectric effect of bone. Furthermore, devices of flexible piezoelectric thin films assembled by SrCO3 mineralized collagen fibrils exhibit a regular open‐circuit voltage of 1.2 V under compressive stress and a stable cycling short‐circuit current of 80 nA under a bending mode. It can also facilitate the development of promising piezoelectric sensors. Abstract : The amorphous strontium carbonate phase infiltrates collagen fibrils and transforms into oriented nanocrystals under its confined‐template effect. The mineralized collagen exhibits the triple piezo‐response coefficient of pure collagen. Furthermore, the collagen films‐based devices can generate a regular open‐circuit voltage of 1.2 V under a compressive stress and a stable cycling short‐circuit current of 80 nA under a bending mode.